Covid-19: A Malediction on the Survival of Daily Wage Labourers - Mohini, Mugdha (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
COVID-19 has come with a single knock as a guest and has settled down as the host who owns everything: life, income, happiness, togetherness, etc. The pace with which the victims of COVID-19 are increasing day by day has become gruesome for the government to control and oblivion for the people to accept as they were hardly conscious of the global situation. The worst victim of this situation is the ‘daily wage labourers’ whose life and family runs because they work on “per day wage system”. In the midst of lockdown in our country, the condition of daily wage labourers has become bad to worst and they are coerced to be stuck in the situation of extreme poverty, hunger, myriad death due to lack of food and complete restlessness. Their life has been seriously jeopardised because of lockdown. The announcement of government’s help is just a relief to the ears but not in actuality as the government herself doesn’t have relevant data of the number of people engaged as daily wage labourers and hence her help does not get channelized appropriately to the needies. The pertinent question that arises here is- Who is responsible for their pathetic situation? The COVID-19? Or the government and her actions? Or the public distribution system which functions here? Or the daily wage labourers themselves? Keywords: COVID-19, Daily wage labourers, Ignored sector, Malediction, Abject poverty, Myriad death, Economic stigma, Overpopulation, Dilemma, Illiteracy